2010
DOI: 10.1097/mbc.0b013e3283333505
|View full text |Cite
|
Sign up to set email alerts
|

Low-molecular-weight heparin and unfractionated heparin in prophylaxis against deep vein thrombosis in critically ill patients undergoing major surgery

Abstract: The objective of the present study was to compare the efficacy and safety of low-dose unfractionated heparin (UFH) and a low-molecular-weight heparin (LMWH) as prophylaxis against venous thromboembolism in critically ill surgical patients undergoing major surgery. This was a randomized prospective study in which critically ill patients scheduled to undergo major elective surgery were allocated to receive subcutaneously either LMWH once daily and a placebo injection containing sterile 0.9% normal saline or 5000… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
39
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 48 publications
(41 citation statements)
references
References 16 publications
2
39
0
Order By: Relevance
“…The observation that the risk of VTE increases as the number of risk factors increases should be taken into account when assessing risk levels and considering thromboprophylaxis (24). The American College of Chest Physicians and the American Society of Colon and Rectal Surgeons have recommended that every hospital should formulate a risk stratification approach to categorize trauma patients in terms of thromboembolic risk (25).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…The observation that the risk of VTE increases as the number of risk factors increases should be taken into account when assessing risk levels and considering thromboprophylaxis (24). The American College of Chest Physicians and the American Society of Colon and Rectal Surgeons have recommended that every hospital should formulate a risk stratification approach to categorize trauma patients in terms of thromboembolic risk (25).…”
Section: Discussionmentioning
confidence: 99%
“…LMWH is among the most significant recent developments in prophylaxis against DVT (24). The anticoagulatory effects of LMWH have been well characterized and function by reducing the activity of coagulation factor XIIa and thrombin (35).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The results demonstrated that both LDUH and LMWH prevent DVT, and the incidence of DVT did not differ significantly between LDUH and LMWH. [16][17][18] Data from an RCT and the metaanalysis, however, showed that LMWH is superior to LDUH in the prevention of pulmonary embolism. 17,18 In another meta-analysis comparing LDUH and LMWH in acutely ill medical patients, LMWH was superior to LDUH in preventing DVT but no difference was found in the incidence of pulmonary embolism.…”
Section: Supporting Evidencementioning
confidence: 99%